Constraints on blue straggler formation mechanisms in galactic globular clusters from proper motion velocity distributions. Issue 1 (9th October 2018) - Leigh, N W C; Panurach, T; Simunovic, M; Geller, A M; Zurek, D; Shara, M M; Sills, A; Knigge, C; Gosnell, N M; Mathieu, R; Puzia, T H; Ventura, J; et al.
ABSTRACT: For a sample of 38 galactic globular clusters (GCs), we confront the observed distributions of blue straggler (BS) proper motions and masses (derived from isochrone fitting) from the BS catalogue of Simunovic & Puzia with theoretical predictions for each of the two main competing BS formation mechanisms. These are mass transfer from an evolved donor on to a main-sequence (MS) star in a close binary system, and direct collisions involving MS stars during binary encounters. We use the FEWBODY code to perform simulations of single–binary and binary–binary interactions. This provides collisional velocity and mass distributions for comparison to the observed distributions. Most clusters are consistent with BSs derived from a dynamically relaxed population, supportive of the binary mass-transfer scenario. In a few clusters, including all the post-core collapse clusters in our sample, the collisional velocities provide the best fit.